What does the corpus callosum tell us about brain changes in the elderly?. (November 2011) - Di Paola, Margherita; Caltagirone, Carlo; Spalletta, Gianfranco
Evaluation of: Ryberg C, Rostrup E, Paulson OB et al. On behalf of the LADIS study group. Corpus callosum atrophy as a predictor of age-related cognitive and motor impairment: a 3 year follow-up of the LADIS study cohort. J. Neurol. Sci. 307(1–2), 100–105 (2011). The corpus callosum is the largest hemispheric interconnection bundle in the human brain. Its anterior–posterior fiber caliber gradient can help in understanding the pathophysiological mechanisms underlying white matter changes both in old age and dementia. Here, the Leukoaraiosis and Disability (LADIS) study, a longitudinal cohort study, which shows an association between corpus callosum atrophy and cognitive and motor decline in the elderly, provides the possibility to consider the use of multimodal macro-microstructural imaging of corpus callosum as a marker of structural brain changes of physiological and pathological aging.